Gestão participativa na inclusão de adultos deficientes visuais - Soares, Claudia Aparecida Morgado (2016)
This study aims to discuss the participation of students with visual impairment in the administrative and pedagogical decisions taken by school managers. In addition, we discuss the attitude of directors towards the visually impaired, that is, as the shares are currently practiced and how they can be expanded to provide the effective inclusion of these students. To develop this work was held initially extensive literature on proposals for educational management and the process of inclusion of blind students and low vision. Applied also, a survey of the visually impaired students, to meet their needs and expectations regarding the posture of managers. Another important factor to consolidate the research was designed and implemented to interview the coordinator and the director of the college, in order to identify inclusive work them before the current educational setting. At the end of this thesis it was found that, although there is the conviviality of the visually impaired with the other students in mainstream schools is not observed their participation in the meetings with school administrators so that they can express their needs and propose measures to facilitate inclusive process